Efektivitas teori konseling cognitive behavior dengan teknik self management untuk meningkatkan disiplin belajar siswa - Putra, I Made; Suarni, Ni Ketut; Dharsana, I Ketut (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
This study aims to determine the effectiveness of cognitive behavior counselingtheory with self-management techniques to increase student learningdiscipline. The design of this study used a Quasi-Experimental Design withnonequivalent post-test control group design. The population of this research isthe tenth grade students of SMA Negeri 2 Singaraja. Sampling was carried outby random sampling class as an intack group. As for the members of thesample are students of class X5 and X6, totaling 79 people as the experimentalclass and the control class. The data analysis method used is the t-hit test usingthe SPSS 25.Windows program. This data collection instrument uses a studydiscipline questionnaire. So this study uses cognitive behavior counselingtheory with self-management techniques to improve learning discipline in classX students of SMA Negeri 2 Singaraja. Based on the results of this studyobtained that cognitive behavior counseling with self management techniqueeffective to increase students learning discipline